VALUES TRANSMISSION THROUGH THE ENGLISH TEXTBOOKS FOR SECONDARY SCHOOL STUDENTS AND ITS INFLUENCE ON THEEIR PERCEPTION OF THE ISLAMIC IDENTITY. RIGS 15-159-0159 - Souad, Merah; Ramdane, Tahraoui; Husin, Nor Hayati (2019)
This research examines the perception of Muslim teachers and students of the values embedded in the English textbooks at the Secondary level of the International Islamic School Malaysia (IISMS). The effect of these values on the students’ vision of an Islamic identity were also analyzed. It is quite impossible to learn English without indulging in its culture. This issue becomes more serious when the textbooks used to teach this language were written in a completely different social and cultural context, alien to the students’ social milieu. To achieve its objectives this study has used firstly, a Literature review was conducted via a reflective analysis in which ideas grouping was made and recommendations were deducted. Secondly, an “Analysis Model” was developed based on little john’s (1998) textbook analysis model. The subject of analysis in this study is the English language textbook used at the International Islamic School Malaysia, Secondary for the 7th, 8th and the 9th grades for the academic year 2018-2019. IISMS offers IGCSE curriculum and uses textbooks written and published in the United Kingdom. Thirdly, an interview of a selected number of students and teachers was conducted as well as a classroom observation. The findings have revealed that the usage of English is expanding in the four corners of the world at the expense of other local languages. Another important finding is that the English language is used as a vessel to spread Western cultural dominance under the pretext of globalization, as it is impossible to strip any language of its cultural context. It was also found that Western values transmission across the English textbooks was explicitly and implicitly manifested. As these textbooks contain a wide range of values that vary from universal to Western. It was also found that; Western values of different sorts such as social, political, philosophical and cultural, were present in the English textbooks at a very high level of density. Another crucial finding in this study has also highlighted, that there is a high level of contradiction between these values and other values propagated in other subjects’ textbooks used by the same students as well as with values propagated by teachers and parents. It was concluded that Muslim students’ perception of Western values vary between acceptance and rejection.